Enabling smart education: An overview of innovations and challenges in modern learning - Koshiry, Amr El; Tony, Mohamed Abd Allah (International Journal of Innovative Research and Scientific Studies, 2025)
Smart education is necessary for ensuring the sustainability of modern education by harnessing technology for enhanced accessibility, productivity, and ecological awareness. This study explores recent innovations such as artificial intelligence (AI), machine learning (ML), and augmented/virtual reality (AR/VR) for enhancing personalized learning and adaptive education systems outlined in the paper. A systematic literature review (2015–2024) elaborates on AI-driven learning analytics, applications of big data, and implications for learning outcomes. Findings indicate that smart education enhances engagement, enables real-time feedback, and provides automated assessments, allowing instructors to identify learning gaps more easily and provide early interventions. In addition, AI-powered tools consolidate digital content to align with learning objectives, enabling more effective instruction. However, challenges such as the digital divide, aging infrastructure, high costs, cybersecurity risks, and reduced social interaction hinder its full implementation. These issues must be resolved through strategic investment in digital infrastructure, cybersecurity policy, and teacher training. Hybrid learning models can also balance digital innovation against conventional interaction to deliver a more comprehensive learning experience. Public-private partnerships are crucial in expanding connectivity and access to resources. By overcoming these challenges, smart education can establish an inclusive, flexible, and technology-enabled learning environment with long-term viability and universal access to quality education.